Practical Measurements for Electric Properties of Polyethylene Nanocomposite Thin Films Under Thermal Conditions - Thabet, Ahmed; Mobarak, Youssef (International Journal of Applied Power Engineering (IJAPE), 2015)
Polymer properties can be experimentally tailored by adding small amounts of different nanoparticles to enhance its mechanical, thermal and electrical properties; thus, it has been widely anticipated that the combination of nanoparticles with traditional resin systems. This paper has been studied the enhancement and controlling electric and dielectric properties of low density polyethylene (LDPE), and high density polyethylene (HDPE) polymer materials by cost-fewer nanoparticles. Certain percentages of clay and fumed silica nanoparticles have been enhanced electric and dielectric properties of polyethylene nanocomposite films. Dielectric spectroscopy has been measured the electric and dielectric properties of each polyethylene nanocomposite with and without nanoparticles at various frequencies up to1kHz under different thermal conditions (20oC and 60oC). Also, it has been investigated the optimum types and percentages of cost-fewer nanoparticles for enhancing electric and dielectric characterization at low and high temperatures.